Viruses Causing Gastroenteritis: The Known, The New and Those Beyond - Bas B. Oude Munnink; Lia van der Hoek (Viruses, 2016)
The list of recently discovered gastrointestinal viruses is expanding rapidly. Whether these agents are actually involved in a disease such as diarrhea is the essential question, yet difficult to answer. In this review a summary of all viruses found in diarrhea is presented, together with the current knowledge about their connection to disease.